The influence of students' and lecturers' attributes and university setting on pre diploma students' English oral proficiency / Nazrul Nadziruddin Mohd Zameri - Mohd Zameri, Nazrul Nadziruddin (2013)
This study is aimed to investigate how variables such as students’ attributes, lecturers’ attributes and university setting influence pre-diploma students’ inclination to use English in the English language classroom. The study is a quantitative study. A sample of 60 prediploma students at UiTM Terengganu (Dungun) was used in this study. Survey method was used to collect data for this study. The findings indicate that students do have positive attributes towards talking in English in class. Besides, it was also found, using descriptive statistics, that students perceive that the lecturer attributes and the university settings are also conducive towards students’ inclination to use English in English language classes. The students’ motivation level was also found to be satisfactory. Inferential statistics using Pearson ‘r’ was used to establish the relationship between student attributes and their motivation level towards talking in English in English classes. It was also found that there existed significant relationships between lecturer attributes and students motivational level towards using English in class. Significant relationships were also found between lecturer attributes and students’ motivational level and also university setting and students’ motivational level when it comes to students’ preponderance towards using English in the class. The findings do suggest that lecturers’ attributes, students’ attributes and university setting do have an influence on students’ oral English proficiency. In view of this more research needs to be done on this area to further confirm the findings. Additionally there should be comparative studies to check on proficiency levels at different universities with differing lecturers’ attributes and setting.